Perbedaan Faktor-faktor yang Mempengaruhi Nilai Perusahaan pada Sektor Industri Dasar Kimia dan Aneka Industri - Imas Restu Prasiwi; Yuli Chomsatu Samrotun; Purnama Siddi (Ekonomis: Journal of Economics and Business, 2023)
The most important component in an entity is the value of the company. This study aims to analyze the factors that can affect company value in the basic chemical industry sector and the various industrial sectors listed on the IDX in 2018-2021. This type of research is quantitative. The data used is in the form of secondary data obtained from the company's financial statements. The population of this study were 129 companies in the basic chemical industry sector and various industrial sectors and obtained a sample of 42 companies taken based on criteria using the purposive sampling method and then tested with multiple linear regression tests. The results of this study show that company size, capital structure, and liquidity have an effect on the firm value of the basic chemical industry sector. Meanwhile, profitability has no effect on the firm value of the basic chemical industry sector. The capital structure variable influences the value of companies in various industrial sectors. Meanwhile, the variable firm size, profitability, and capital structure have no effect on firm value in various industrial sectors